2019
DOI: 10.3390/ma12213486
|View full text |Cite
|
Sign up to set email alerts
|

Penetration Behavior of High-Density Reactive Material Liner Shaped Charge

Abstract: The traditional polytetrafluoroethylene (PTFE)/Al reactive material liner shaped charge generally produces insufficient penetration depth, although it enlarges the penetration hole diameter by chemical energy release inside the penetration crater. As such, a novel high-density reactive material liner based on the PTFE matrix was fabricated, and the corresponding penetration performance was investigated. Firstly, the PTFE/W/Cu/Pb high-density reactive material liner was fabricated via a cold pressing/sintering … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…Wang et al [13] carried out a series of experiments at stand-offs of 1.0, 2.0 and 2.5 CD to determine the influence of PTFE/Al reactive liner thickness on the penetration performance of the shaped charge. Guo et al [14] fabricated a novel high-density reactive material liner based on the PTFE matrix and investigated the corresponding penetration performance. The static experimental results demonstrated that the penetration depth of this high-density reactive jet increased firstly and then decreased by increasing the stand-off.…”
Section: Introductionmentioning
confidence: 99%
“…Wang et al [13] carried out a series of experiments at stand-offs of 1.0, 2.0 and 2.5 CD to determine the influence of PTFE/Al reactive liner thickness on the penetration performance of the shaped charge. Guo et al [14] fabricated a novel high-density reactive material liner based on the PTFE matrix and investigated the corresponding penetration performance. The static experimental results demonstrated that the penetration depth of this high-density reactive jet increased firstly and then decreased by increasing the stand-off.…”
Section: Introductionmentioning
confidence: 99%
“…Liu [ 14 ] used the grey system theory to analyze the influence laws of the related parameters on the formation of EFPs. In addition, many new materials have been applied to the liner of shaped charges [ 15 , 16 , 17 , 18 ], which improves the penetration capability and damage aftereffect of shaped charges. Müller [ 19 ] proved through experimental research that detonation waves in SCWS collide with each other and meet certain conditions that will form a Mach wave and produce overdriven detonation.…”
Section: Introductionmentioning
confidence: 99%
“…According to the prior simulation estimation, the times of jet head reaching 1 CD (charge diameter) standoff (the distance between the jet head and the initial position of the liner bottom) and 2 CD standoff were obtained. It should be noted that, since the damage effect of the reactive material jet is greatly influenced by the standoff, and the optimum standoff of reactive material jet is about 1 CD-2 CD [20], thus the times corresponding to these two standoffs are selected. The two different times were then set for the two ray tubes as ray emission delay times, where the initial time corresponds to the moment of the detonator being initiated.…”
Section: Experiments Setupmentioning
confidence: 99%